Synthesis and Characterization of Some New 1,3,4-Oxadiazole and 1,2,4-Triazole Derivatives Based on 3,4,5,6 Tetrachlorophthalimide - Al-Azzawi, Ahlam; Hammud, Kafa (Iraqi Journal of Science, 2024)
Several new derivatives of 1,3,4-oxadiazoles and 1,2,4-triazoles linked to 3,4,5,6-tetrachlorophthalimide moiety were synthesized through following multisteps. The first step involved preparation of 3,4,5,6-tetrachlorophthalimide via reaction of 3,4,5,6-tetrachlorophthalic anhydride with urea at high temperature. Treatment of the resulted imide with ethyl chloroacetate in the second step afforded tetrachlorophthalimidyl ester which inturn was introduced in reaction with hydrazine hydrate in the third step, producing the corresponding acetohydrazide. The synthesized acetohydrazide was introduced in different synthetic paths including treatment with phenyl isothiocyanate or reaction with carbon disulfide in alkaline solution then with hydrazine hydrate to afford the new 1,2,4-thiazoles, while introducing of acetohydrazide in reaction with carbon disulfide in alkaline solution under reflux or in reaction with benzaldehyde producing a new Schiff base. Treatment of the new Schiff base with acetic anhydride afforded the new 1,3,4-oxadiazoles.